The Impact of Suggested Dosage Percentage of NPK Fertilizer and Biofertilizer on the Growth and Production of Inpari 32 Rice Variety (Oryza sativa L.) - Lia Amalia; Danu Hamidi; Nunung Sondari; Tien Turmuktini; Budiasih Budiasih (Jurnal Agrosci, 2026)
The study was conducted at the Agricultural, Fisheries, and Forestry Extension Agency (BP3K) in Cilamaya Wetan District, Karawang Regency, West Java, at an elevation of 8.9 m above sea level, from December 2022 to March 2023. Aims. The research focuses on exploring how the recommended percentage of NPK fertilizer interacts with biological fertilizer to affect the growth and yield of the lowland rice variety Inpari 32 and to determine the ideal biological fertilizer for each NPK dose level that maximizes grain weight per plot. Methods. The experimental design used was a factorial pattern, a Randomized Block Design with two factors and repeated three times. The first factor is the dose of NPK fertilizer (N), which includes three treatment levels, namely: n1 = 100% of the suggested dose (500 g plot-1); n2 = 50% of the suggested dose (250 g plot-1), and n3 = 25% of the suggested dose (125 g plot-1). The second factor is the biological fertilizer dose (H), which includes 3 treatment levels, namely: h1 = 0% of the recommended dose (0 g plot-1); h2 = 50% of the recommended dose (15 g plot-1), and h3 = 100% of the recommended dose (30 g plot-1). Result. The experimental results indicated an interaction between the recommended percentage of NPK fertilizer and biological fertilizer regarding plant height and number of tillers aged 28 Days After Planting (DAP), 42 DAP, and 56 DAP, along with the number of productive tillers, panicle length, grain weight per panicle, grain weight per clump, and grain weight per plot. The highest grain weight per plot of 24.32 kg was attained at the advised NPK fertilizer dosage of 100%, along with the ideal recommended biological fertilizer dose of 66,10% (r2 = 0.92). Conclusion. The suggested NPK fertilizer dosage of 50% yielded the highest grain weight per plot of 23.77 kg, using the ideal recommended biological fertilizer amount of 60.19% (r2 = 0.90). Implication. With a suggested application of NPK fertilizer of 25%, the highest grain mass per plot of 23.15 kg at an ideal biological fertilization rate of 55.10% (r2 = 0.94).